Maternal Responsive Parenting Trajectories From Birth to Age 3 and Children’s Self-Esteem at First Grade - Kim, Yeon Ha (Frontiers in Psychology, 2022)
This paper examines the quality and stability of the responsive parenting practices of mothers with infants and the longitudinal links between these practices and children’s self-esteem. Using data presented by the Panel Study on Korean Children, this study identified Korean mothers’ responsive parenting trajectories from birth to age three and examined their associations with children’s self-esteem at first grade. Korean mothers developed one of three responsive parenting patterns from birth to age three: low (19.0%), moderate (66.0%), or high (15.0%). Children’s self-esteem differed according to their mother’s responsive parenting trajectory. First-graders with mothers displaying the low responsive parenting trajectory were more likely to have lower self-esteem than children of mothers with the moderate responsive parenting trajectory and children of mothers with the high responsive parenting trajectory. The longitudinal link between mother-reported responsive parenting patterns during infancy and child-reported self-esteem at first grade was verified. This finding highlights the significance of early responsive parenting from mothers as a predictor of the self-esteem of children in later developmental stages.